KEBIJAKAN FISKAL NEGARA INDONESIA DALAM PERSPEKTIF EKONOMI ISLAM - Setiady, Tri (Universitas Wiralodra, 2023)
Fiscal policy is defined as the policy action taken by the government, which is related to the opinion and spending of money. What is meant here is the management of state revenues and expenditures carried out by the government of a country. Indonesia's fiscal policy is reflected in the State Expenditure Opinion Budget (APBN). In the APBN, there is a government stipulation regarding the allocation and distribution of state finances. In Islamic countries, the management of state finances is handled by Bayt al-mal. Bayt al-Mal is the same as the Ministry of Finance which deals with financial matters and matters related to the state treasury. Even though Bayt al-mal was institutionally formed by the caliph 'Umar ibn Khattab. In fact, the country's fiscal policy was implemented during the time of the Prophet SAW. Al-Quran and as-Sunnah often allude to the country's fiscal policy. Among other things: the management of zakat by the state, collection of al-jizyah from the people of the book, the enactment of al-fay 'and al-ghanimah laws, as well as the Prophet's policy of public ownership.